The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajpheart.00790.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral vascular disease risk progressively constrains perfusion adaptability in the skeletal muscle microcirculation

Abstract: -To determine the impact of progressive elevations in peripheral vascular disease (PVD) risk on microvascular function, we utilized eight rat models spanning "healthy" to "high PVD risk" and used a multiscale approach to interrogate microvascular function and outcomes: healthy: SpragueDawley rats (SDR) and lean Zucker rats (LZR); mild risk: SDR on high-salt diet (HSD) and SDR on high-fructose diet (HFD); moderate risk: reduced renal mass-hypertensive rats (RRM) and spontaneously hypertensive rats (SHR); high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 62 publications
6
50
0
Order By: Relevance
“…The significant inverse correlation observed between muscle oxygenation and microvascular reactivity indices during arterial occlusion, with the force maintained during the handgrip task, agrees with results in hypertensive rodents, showing a link between skeletal muscle microvascular dysfunction and alterations in performance outcomes. 12 Whether patients with more severe hypertension would be unable to achieve perfusion and exhibit faster signs of exercise intolerance requires further investigation.…”
Section: Muscle Oxygenation and Bp Responses During Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…The significant inverse correlation observed between muscle oxygenation and microvascular reactivity indices during arterial occlusion, with the force maintained during the handgrip task, agrees with results in hypertensive rodents, showing a link between skeletal muscle microvascular dysfunction and alterations in performance outcomes. 12 Whether patients with more severe hypertension would be unable to achieve perfusion and exhibit faster signs of exercise intolerance requires further investigation.…”
Section: Muscle Oxygenation and Bp Responses During Exercisementioning
confidence: 99%
“…50 Postulated mechanisms for these dysfunctions include: (1) the capillary rarefaction and increased perfusion heterogeneity in hypertensives impair flow and oxygen delivery to the working muscles; thus, a greater increase in BP is required to achieve perfusion, and (2) the structural alterations in the resistance vasculature may act as a vascular amplifier that further enhances the effects of a hypertensive stimulus, such as exercise. 12,50 In addition, the impaired oxidative capacity suggestive of mitochondrial dysfunction/uncoupling in the skeletal muscle of hypertensive patients could lead to an increase in reactive oxygen species, reducing endothelial NO synthase, and resulting in a decrease NO bioavailability. 46 The increased oxidative stress and inflammation further reduces NO, promoting endothelial dysfunction within the small vessels' wall and impairing vasodilation in exercising muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Frisbee and others [2] have shown that attenuation of these flow patterns may be a major contributor to disease risk. They argue that if we are to understand network functionality and flexibility in cardiovascular (CV) and metabolic (Met) disease it is important to obtain quantitative in vivo information on the temporal behaviour and spatial distribution of microvascular perfusion.…”
mentioning
confidence: 98%
“…More recently, chaotic network attractor analysis [17,18] has revealed a declining adaptability of microvascular flow patterns in rodent models of CV and Met disease [2]. However, the relationship between the non-linear oscillatory dynamics of the BF signal, microvascular network perfusion heterogeneity and adaptability (and their impact on microvascular pathology) has yet to be fully elucidated.…”
mentioning
confidence: 99%